2019
DOI: 10.1016/j.jddst.2019.101164
|View full text |Cite
|
Sign up to set email alerts
|

Personalized 3D printed ciprofloxacin impregnated meshes for the management of hernia

Abstract: This study aims to explore the application of fused deposition modeling (FDM), a widely used 3D printing technique, in the fabrication of personalised hernial meshes. Eight different meshes with and without the loading of an antibiotic (ciprofloxacin HCl) were designed using two different polymers, polypropylene (PP) and polyvinyl alcohol (PVA), having different pore size, shape and thread thickness. Printed meshes were evaluated for their mechanical, drug loading and release characteristics. Among the fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…However, these works were not realistic due to material selection, but these studies worked as a proof of concept showing the potential of 3D printing for this purpose. Additionally, some recent work described the potential of using FDM as a tool for mesh implant manufacturing using PP [50]. The limitations of this material have been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…However, these works were not realistic due to material selection, but these studies worked as a proof of concept showing the potential of 3D printing for this purpose. Additionally, some recent work described the potential of using FDM as a tool for mesh implant manufacturing using PP [50]. The limitations of this material have been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…However, the obvious challenge is their manufacturing process as fabricating smaller batches of medicines, especially designed for individual patients, can be problematic, time-consuming and costly. However, the recent emergence of 3D printing technologies has given pharmaceutical scientists a way forward to develop personalised medicines and devices [ 24 , 25 , 26 , 27 , 28 , 29 ]. The current project, therefore, is aimed at addressing the limitations as mentioned above by developing additively manufacturing fast-dissolving captopril tablets.…”
Section: Introductionmentioning
confidence: 99%
“…The time needed for proper swelling of the filament greatly affects the drug loading [ 19 ]. The soaking duration can vary between 12 h, as reported by Qamar et al [ 20 ] up to 3–4 days, as reported by Ibrahim et al [ 21 ]. In this process, a commercial filament can be used, which is the main advantage of this approach.…”
Section: Resultsmentioning
confidence: 96%
“…Farto-Vaamonde et al [ 49 ] and Costa et al [ 47 ] worked on producing drug-loaded scaffolds for tissue engineering and regeneration medicine. Qamar et al [ 20 ] and Teo et al [ 27 ] produced drug-loaded meshes for eradicating bacterial infections. Horst et al [ 45 ] discussed producing disks for testing antibacterial activity of oleo-gum-resin loaded with nano-oxides.…”
Section: Resultsmentioning
confidence: 99%